2022
DOI: 10.1007/s11882-022-01057-8
|View full text |Cite
|
Sign up to set email alerts
|

Immune Metabolism in TH2 Responses: New Opportunities to Improve Allergy Treatment — Disease-Specific Findings (Part 1)

Abstract: Purpose of Review Recent high-level publications have shown an intricate connection between immune effector function and the metabolic state of the respective cells. In the last years, studies have begun analyzing the metabolic changes associated with allergies. As the first part of a two-article series, this review will briefly summarize the basics of immune metabolism and then focus on the recently published studies on metabolic changes observed in allergic patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 94 publications
(145 reference statements)
0
9
0
1
Order By: Relevance
“…Metabolism represents a highly intricate and multifaceted network of biochemical reactions, which are orchestrated with the purpose of endowing the cell with the appropriate molecules at the appropriate moment. To expound, the intricate process of metabolism involves the breakdown of glucose, fatty acids, and amino acids with the intention of generating both energy in the form of ATP and metabolites that serve as the essential building blocks of various cellular pathways and components (14). To meet the energy demands of cellular processes, glucose undergoes a complex enzymatic process called glycolysis, consisting of multiple sequential reactions that yield two molecules of pyruvate and two molecules of ATP.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Metabolism represents a highly intricate and multifaceted network of biochemical reactions, which are orchestrated with the purpose of endowing the cell with the appropriate molecules at the appropriate moment. To expound, the intricate process of metabolism involves the breakdown of glucose, fatty acids, and amino acids with the intention of generating both energy in the form of ATP and metabolites that serve as the essential building blocks of various cellular pathways and components (14). To meet the energy demands of cellular processes, glucose undergoes a complex enzymatic process called glycolysis, consisting of multiple sequential reactions that yield two molecules of pyruvate and two molecules of ATP.…”
Section: Discussionmentioning
confidence: 99%
“…This selective catabolism of glucose to lactate is known to disrupt the Krebs cycle, as a consequence of inadequate pyruvate supply to the mitochondria. This impairment leads to specific arrest points in the Krebs cycle, which consequently results in the accumulation of intermediary metabolites (14). For example, research on macrophages stimulated with LPS has revealed that these arrest points occur downstream of citrate and succinate (21, 22).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Over the past three years, immune metabolism studies in allergies have found that asthma is associated with increased aerobic glycolysis ( Goretzki et al, 2023 ). A study of serum lactate acid levels in clinically stable patients with allergic asthma, healthy controls, and patients with chronic obstructive pulmonary disease (COPD) found that its content was substantially higher in patients than in healthy controls, which was also significantly higher than that in controls of patients with COPD ( Ostroukhova et al, 2012 ) suggesting an increase in glycolysis.…”
Section: Introductionmentioning
confidence: 99%
“…Asthma is a chronic inflammatory process of the lower respiratory airways and a Type 2-high (Th2) disease [ 35 ]. Some researchers believe that GA may be involved in immune function by affecting the balance of Th1 and Th2 in favor of Th1 responses [ 36 ] or stress responses caused by surgery [ 37 ].…”
Section: Introductionmentioning
confidence: 99%